Pengaruh Harga Dan Diferensiasi Produk Terhadap Keputusan Pembelian Sepeda Motor Suzuki Satria Fu di Medan Sumatera Utara - Ira Arnie Yuvira; M. Yamin Siregar; Hesti Sabrina (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2021)
This study aims to determine “The Influence of Price and Product Differentiation Against Buying Decision Suzuki Satria Fu Motor Cycle at Suzuki Sunindo Amplas Medan Branches”. This type of research is associative is a research that is asking the relationship between two variables. And by using the technique of slovin formula, then the number of samples in this study as many as 111 the price variable has a positive and significant effect on buying decision variable has a positive and significant effect on buying decisionhence trust variable partially have positive and significant influence to buyng decisions. Based on F test result, it is obtained F count value  of 2.908 2.694 with sig 0.013 0.05  , show Ho rejected and Ha accepted, meaning price and product differentiation simultaneously have positive and significant effect to variable buying decision. R Square value obtained of 0.834. To see the big influence of independent variable to dependent variable by calculating coefficient of determination (KD) = R2 x 100%, So obtained  KD= 83.40% of buying decision (dependent variable) can be explained by price and product differentiation. The remaining 16.60% is influenced by oter factors not described in this study.